Early-life adversity and adolescent depression: mechanisms involving the ventral striatum. (16th December 2014) - Goff, Bonnie; Tottenham, Nim
<x content-type="archive" xml:space="preserve">Abstract</x> Early-life adversity is a well-established risk factor for the development of depression later in life. Here we discuss the relationship between early-life adversity and depression, focusing specifically on effects of early-life caregiver deprivation on alterations in the neural and behavioral substrates of reward-processing. We also examine vulnerability to depression within the context of sensitive periods of neural development and the timing of adverse exposure. We further review the development of the ventral striatum, a limbic structure implicated in reward processing, and its role in depressive outcomes following early-life adversity. Finally, we suggest a potential neurobiological mechanism linking early-life adversity and altered ventral striatal development. Together these findings may help provide further insight into the role of reward circuitry dysfunction in psychopathological outcomes in both clinical and developmental populations.